Chemical Compositions, Antimicrobial and Therapeutic Properties of Essential Oils of Dennettia tripetala - Ekandem, Joachim J.; Udourioh, Godwin A.; Obi, Leonard K.; Solomon, Moses M. (Current Analytical Chemistry, 2025)
BackgroundIt is well-known that essential oils are a rich source of bioactive components and are traditionally used as one of the alternatives to conventional medicines for treating various diseases and symptoms. Like other natural products, they are safe but should be used with care since all substances have potential toxicity depending on the conditions of exposure, the dose, and the route of administration.MethodsThis manuscript studies the chemical composition and antimicrobial properties of essential oil derived from D. tripetala. The essential oil was extracted from fresh D. tripetala fruits using steam distillation and subsequently subjected to Fourier Transform Infrared Spectroscopy (FT-IR) and Gas Chromatography-Mass Spectrometry (GC-MS) analyses. The antimicrobial potential of the essential oil was evaluated against a panel of microorganisms, namely Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Pseudomonas aeruginosa, Candida albicans, and Aspergillus niger.ResultsThe GC-MS analysis unveiled a diverse array of compounds within the essential oil, with the notable constituents being linalool, benzyl nitrile, benzene (2-nitroethyl), bicyclo(4.2.0)octa-1,3,5-triene, 1,3,7-Octatrien-5-yne, styrene, butylated hydroxytoluene, and Nerolidol 2. D. tripetala essential oil significantly inhibits the microbial activities of all the tested organisms. It exhibits inhibitory activity against Bacillus subtilis and Escherichia coli at a MIC value of 12.5%, Staphylococcus aureus, and Pseudomonas aeruginosa at a MIC value of 25%, Candida albicans at a MIC value of 50%, and Aspergillus niger at MIC value 25%. The strongest inhibition of the oil is against Klebsiella pneumoniae at a MIC value of 3.12%.ConclusionThis research posits that the ethnomedicinal value ascribed to the essential oil of D. tripetala can be attributed to the presence of the identified compounds, some of which are already recognized for their biological activities. The essential oil presents promising potential as a source of lead compounds for developing anti-infective drugs, particularly those targeted against Klebsiella pneumoniae.
Keywords: therapeutic properties